Original paperLoss of asthma control after cessation of omalizumab treatment: real life data - Kupryś-Lipińska, Izabela; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Many clinical and observational studies have demonstrated effectiveness of omalizumab (OMA) in the treatment of severe asthma, but the optimal duration of the therapy remains unknown. Aim: The article presents the authors’ clinical experience on OMA cessation in routine practice. Material and methods: Due to new reimbursement criteria, OMA therapy has been interrupted in 11 subjects (6 women/5 men). The mean age of patients was 50.73 ±14.16 years, the mean time of severe asthma duration was 13.54 ±6.05 years. All of them had an excellent/good response to OMA. The duration of OMA therapy was 67.73 ±11.64 months. Results: Nine out of 11 patients had severe asthma exacerbation within the first 5 months after the OMA withdrawal. The mean time to the first severe exacerbation was 7.56 ±2.67 weeks. Between the time of OMA cessation and the time of reassessment, the mean score of Asthma Control Questionnaire increased from 2.58 ±0.71 to 3.63 ±1.26 points and the mean score of Asthma Quality of Life Questionnaire decreased from 4.3 ±1.91 to 3.18 ±1.17 points. The mean oral corticosteroids (OCS) dose increased from 4.61 ±3.0 mg/day to 33.33 ±13.12 mg/day. The number of exacerbations within the last 12 months increased from 1.6 ±0.67 to 5.2 ±1.4, and the number of hospitalizations or emergency room (ER) attendence increased from 0.11 ±0.31 to 1.56 ±1.26. Conclusions : These data indicate that the withdrawal of OMA therapy after the successful long-term therapy may cause severe asthma exacerbations. Therefore, the decision regarding cessation of OMA treatment should be undertaken individually after careful weighing benefits and risks, especially in patients with a long history of severe asthma, treated with high doses of OCS before OMA introduction, near-fatal asthma events and/or aggravation of asthma during previous episodes of interruptions in OMA treatment.